VEGFR-3 Signaling Regulates Triglyceride Retention and Absorption in the Intestine - Shew, Trevor; Wolins, Nathan E.; Cifarelli, Vincenza (Frontiers in Physiology, 2018)
The lymphatic system is an important conduit for the transport of dietary lipids absorbed in the enterocytes, packaged into lipoproteins as chylomicrons, and delivered to the bloodstream. Once considered a passive drainage, chylomicrons entry into intestinal lymphatic vessels, or lacteals, is now emerging to be an active process controlled by a dynamic and complex regulation. Vascular endothelial growth factor(VEGF)-C, a major lymphangiogenic factor, regulates lacteal maintenance and function. Little is known about the role of its cognate tyrosine kinase VEGF receptor 3 (VEGFR-3) during lipid absorption. Here we investigated role of VEGFR-3 signaling in lipid absorption and distribution into tissues using the Chy mouse model, which bears an inactivating mutation in the tyrosine kinase domain of VEGFR-3 (heterozygous A3157T mutation resulting in I1053F substitution). Our data show that inactivation of VEGFR-3 tyrosine kinase motif leads to retention of chylomicrons in the small intestine, decreased postprandial levels of triglycerides (TGs) in the plasma and increased excretion of lipids into their stools. We further show that levels of nitric oxide (NO), required for chylomicron mobilization into the bloodstream, are significantly reduced in the Chy intestine after a fat bolus suggesting a critical role for VEGFR-3 signaling in the generation of NO during lipid absorption. Our data support the hypothesis that VEGFR-3 signaling plays an important role in chylomicron entry into lacteals and trafficking to peripheral tissues.